Glacier mass variations in the China-Pakistan highway regions from multi-source altimetric remote sensing data - Yanchao Zheng; Weibing Du; Yangyang Li; Huabin Chai; Abhishek Banerjee (Geocarto International)
The increasing frequency of extreme climatic events has significantly impacted glacier dynamics across diverse regions. This study utilizes ICESat-2 data and Digital Elevation Models (DEMs) to analyze glacier elevation trends along the China-Pakistan Highway (CPH). Systematic DEM evaluations identified NASA DEM as the optimal dataset (30 m resolution), showing minimal deviation and strong alignment with ICESat-2. Glaciers in the CPH exhibited a weakly positive mass balance (+0.28 ± 0.05 m w.e. yr−1), most pronounced in Karakorum, reaffirming the Pamir-Karakorum anomaly. Regional climate trends revealed temperature (+0.04 ± 0.03 °C yr−1) and precipitation (+0.08 ± 0.03 mm yr−1) increases, with distinct north-south temperature gradients and monsoonal-driven precipitation in East Pamir and West Karakorum. Combined climatic variability and glacier surges heightened glacier-related hazards, driven by complex topography and atmospheric interactions..